Integrated strategies on sustainable development, climate change mitigation and adaptation in Western Europe: communication rather than coordination. (13th December 2013) - Casado-Asensio, Juan; Steurer, Reinhard
Abstract: Complex environmental challenges cut horizontally across sectors and vertically across levels of government. To address them in coordinated and integrated ways, governments have resorted to integrated, multi-sectoral strategies since the 1990s. After introducing this new governance approach, we describe the policy rationale, prevalence, governance characteristics and performance of three distinct yet thematically related, integrated strategies on sustainable development, climate change mitigation and adaptation in the EU-15 countries. Based on this literature-based synthesis, we highlight their similarities and differences and the lack of linkages between them. The concluding discussion explores options on how to develop integrated strategies further. Since all three integrated strategies failed as comprehensive governing processes that aim to better coordinate policies, we suggest recalibrating them towards communication so that they can be more effective in pursuing the functions they can realistically fulfil: providing direction and raising awareness.